2019
DOI: 10.1177/1359105319869804
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships between childhood abuse history, attachment, and health anxiety

Abstract: This study examined the relationship between childhood abuse experiences and health anxiety in adulthood and investigated the role of attachment in this relationship. In total, 181 university students (aged 18–29 years) completed a battery of measures that assessed childhood abuse, health anxiety, and attachment orientation. Health anxiety was associated with all categories of childhood abuse and overall childhood abuse severity. Anxious attachment partially mediated the relationship between overall childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
(76 reference statements)
2
5
1
Order By: Relevance
“…Although early childhood adversity has been directly linked to health anxiety in previous research (Reiser et al, 2019 ), the present study did not find a direct association. Instead, illness appraisals were found to be a mechanism by which ACEs affect emerging adults’ health-related adjustment.…”
Section: Discussioncontrasting
confidence: 96%
“…Although early childhood adversity has been directly linked to health anxiety in previous research (Reiser et al, 2019 ), the present study did not find a direct association. Instead, illness appraisals were found to be a mechanism by which ACEs affect emerging adults’ health-related adjustment.…”
Section: Discussioncontrasting
confidence: 96%
“…Reliability: the weighted-kappa coefficient for the ACE score (range: 0-8) was 0.64 (95% CI, 0.36-0.60), indicating good test-retest reliability. 21,22 Convergent Validity: The findings of this study 23 supported ACE-IQ's reliability (Cronbach's alpha = 0.854), convergent validity (r = 0.85, p .001 with the CTQ-SF), predictive validity (R2 = 0.12, p = .001 of the SHI total score) and discriminant validity (F-value = 13.90, p .001).…”
Section: Adverse Childhood Experiences Scalesupporting
confidence: 56%
“…Reliability : the weighted-kappa coefficient for the ACE score (range: 0–8) was 0.64 (95% CI, 0.36–0.60), indicating good test-retest reliability. 21, 22…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field, studies have shown that youths with secure attachment showed more adaptive strategies when faced with a fearful situation, tending to seek comfort and emotional support from parents and friends [41,42]. Conversely, insecure attachment adolescents tend to use maladaptive responses in facing a stressful life event [43,44], showing higher anxiety levels [45], and post-traumatic stress disorder symptoms [46]. Recently, studies have shown that the quality of attachment may also influence individuals' experience of fear during the COVID-19 pandemic and the resulting psychopathological outcomes [44,[47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%